Analisis Peran Kebijakan dalam Membangun Budaya Organisasi yang Kolaboratif - Dea Aulia Cintiara; Imaduddin Akhyar; Rizka Putri Ramadhani; Al Qori Maulida Putri; Soca Permana Bardian (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
In facing complex challenges in an era of rapid change, modern organizations are required to build a collaborative culture to increase innovation and productivity. This research aims to analyze the role of organizational policies in shaping a collaborative culture, the factors supporting its success, and the challenges faced. Using the Systematic Literature Review (SLR) method that focuses on the 2019-2024 literature, data was collected through searching for certain keywords and a selection process based on relevance and quality, resulting in 8 articles relevant to this research. The results showed that organizational policies play an important role in creating a collaborative culture through strengthening the values of openness, trust, and communication. In addition, the successful implementation of policies influenced by collaborative culture in organizations is driven by many interrelated factors, which include interaction history, incentives for participation, power distribution, leadership, institutional design, face-to-face dialogue, and management support. The main challenges in implementing collaborative policies include ineffective leadership, lack of trust between organizations, poor communication, task dependency that requires high coordination, goal differences, resource limitations, rigid regulations, and organizational cultural conflicts. Resistance to change and difficulty managing conflict are also major obstacles.